Structural and Functional Organization of the Synapse - Hell, Johannes W.; Hell, Johannes W.; Ehlers, Michael D.; Ehlers, Michael D. (Springer US : Imprint: Springer, 2008)
Synapses play a central role in the brain by mediating signal transmission between neurons. This book provides a fundamental description of the synapse by leading experts in the field. Each individual synapse carries out its numerous functions in a tiny space, thereby requiring an exquisite molecular and functional arrangement. This book describes the molecular structure and cellular function of central synapses in the brain, providing a detailed view of the brain’s fundamental unit of information storage.